Lo scandaloso rifiuto della sposa. L'ombra del matrimonio riparatore nel cinema italiano prima e dopo il caso Franca Viola (Schermi. Storie e culture del cinema e dei media in Italia, 2022)
In 1965 Franca Viola, an unknown teenager from the small Sicilian village of Alcamo, declined to marry the man who had kidnapped and raped her. By ignoring a law that still cleared rapists if they accepted to marry their victims, Viola’s impressive behaviour made a mediatic and judicial fuss that spread all over Italy. The unease raised by the old tradition of the “shotgun wedding” was testified not only by the newspapers reports from that time but also by the post-war cinematic production. Between the 1950s and the 1960s the topic is widely explored in the film industry, both in melodramatic productions and in comedies and even in bitterly farcical movies. By analysing the mediatic output of the Viola case and the legal debate it issued, this contribution will focus on the representations of the “shotgun wedding” in the films produced before and after the shocking case of the young Sicilian woman.
Keywords: Franca Viola; Elopement; Italian press; Shotgun wedding; Honour code